New records of genus Culicoides Latreille from Oaxaca, Mexico (Diptera: Ceratopogonidae) - Huerta, Herón; Benítez-Alva, José Ismael; Concha-Suarez, Jorge; Ibáñez-Piñón, Clemente R.; Manrique-Saide, Pablo (Instituto de Ecología, A.C., 2020)
First records of Culicoides ginesi and Culicoides glabellus for Mexico. New distribution records for the state of Oaxaca of the following species are also presented: Culicoides baueri, Culicoides debilipalpis, Culicoides hylas, Culicoides neopulicaris, Culicoides pseudodiabolicus and Culicoides pusillus. Also, new localities for Culicoides foxi, Culicoides insignis, Culicoides jamaicensis and Culicoides ocumarensis are included. A key and table are presented for the known species in the state of Oaxaca.